2015
DOI: 10.1152/jn.00418.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cadence-dependent changes in corticospinal excitability of the biceps brachii during arm cycling

Abstract: This is the first study to report the influence of different cadences on the modulation of supraspinal and spinal excitability during arm cycling. Supraspinal and spinal excitability were assessed using transcranial magnetic stimulation of the motor cortex and transmastoid electrical stimulation of the corticospinal tract, respectively. Transcranial magnetic stimulation-induced motor evoked potentials and transmastoid electrical stimulation-induced cervicomedullary evoked potentials (CMEPs) were recorded from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…Vertex was determined by measuring the mid-point between the participant’s nasion and inion, and the mid-point between the participant’s tragi. The intersection of these two points was measured, marked and defined as vertex (Forman et al, 2014, 2015, 2016b; Pearcey et al, 2014; Copithorne et al, 2015; Philpott et al, 2015). The coil was held tangentially to the participant’s skull (approximately parallel to the floor) with the direction of the current flow preferentially activating the left motor cortex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertex was determined by measuring the mid-point between the participant’s nasion and inion, and the mid-point between the participant’s tragi. The intersection of these two points was measured, marked and defined as vertex (Forman et al, 2014, 2015, 2016b; Pearcey et al, 2014; Copithorne et al, 2015; Philpott et al, 2015). The coil was held tangentially to the participant’s skull (approximately parallel to the floor) with the direction of the current flow preferentially activating the left motor cortex.…”
Section: Methodsmentioning
confidence: 99%
“…Because changes in MEP and CMEP amplitudes can be the result of changes to the Mwave, both MEPs and CMEPs were normalized to the Mwaves evoked during the same experimental condition. Pre-stimulation EMG was measured from rectified traces and was defined as a 50 ms window of the mean rectified EMG immediately prior to the stimulation artifact (Forman et al, 2014, 2015, 2016b). Measurements were taken from the averaged files of all eight MEPs or all eight CMEPs.…”
Section: Methodsmentioning
confidence: 99%
“…Considerably less information is currently available regarding corticospinal excitability (CSE) modulation during locomotor outputs, though we are beginning to understand CSE modulation during leg [7,12,13] and arm cycling [8,14,15,16]. CSE can be assessed by measuring the amplitude of motor evoked potentials (MEPs) elicited via transcranial magnetic stimulation (TMS) of the motor cortex and transmastoid electrical stimulation (TMES) of corticospinal axons.…”
Section: Introductionmentioning
confidence: 99%
“…CSE can be assessed by measuring the amplitude of motor evoked potentials (MEPs) elicited via transcranial magnetic stimulation (TMS) of the motor cortex and transmastoid electrical stimulation (TMES) of corticospinal axons. Together, these measures give an indication of supraspinal and spinal excitability [8,14,16,17,18,19]. Using these techniques, Sidhu and colleagues have recently shown that CSE is phase-, muscle- and intensity-dependent to the leg muscles during cycling [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation